A digitally driven pixel circuit with current compensation for AMOLED microdisplays. Issue 9 (29th January 2015) - Ji, Yuan; Ran, Feng; Xu, Hongguang; Shen, Weixin; Lilja, David J.
Abstract A novel digitally driven pixel circuit for active‐matrix organic light‐emitting diode (OLED) microdisplays is proposed and evaluated. This circuit supports both pulse width modulation and pulse density modulation digital drive approaches. Only three transistors and one capacitor are required per pixel for the proposed circuit. A current mirror is used to compensate for the pixel current changes that occur because of the degradation of the OLEDs over time. The compensation current depends on the potential of the common cathode, the properties of the current mirror, and the Width/Length (W/L) ratio of the drive transistor. The proposed digital pixel circuit also has advantages in circuit layout compared with analog pixel circuits.